Postweaning Performance of the Agouti (Dasyprocta leporina): A Neotropical Rodent with Potential for Domestication - Hannah-Marie Samantha Singh; Kegan Romelle Jones (Veterinary Medicine International)
This project aimed to observe the effect of different weaning times on the weight gain in agouti (Dasyprocta leporina). The goal was to acquire an appropriate weaning time for offsprings. The experiment was performed at the University of the West Indies Field Station Farm (UFS) where animals were divided into four treatment groups, with each treatment group consisted of four animals. Treatment 1 offsprings were weaned at four weeks, treatment 2 offsprings were weaned at three weeks, treatment 3 offsprings were weaned at two weeks, and treatment 4 offsprings were weaned at one week. The offsprings were raised experimentally for their first seven weeks. There was no significant difference (p>0.05) recorded in offsprings live weight and average daily gain (ADG) for treatments 1, 2, and 3. However, offsprings reared in treatment 4 had significantly (p<0.05) less live weight and weight gain in comparison to the other groups at seven weeks. Offsprings in treatment 4 also experienced 50% mortality (2/4 animals died), one animal removed from the experiment due to progressive weight loss, and one offspring remained in the experiment for its duration. The other treatment experienced no loss (0% mortality). Based on the results of the experiment, agouti offsprings should not be weaned at one week due to high mortality and low live weight at the end of seven weeks. Animals can be weaned between 2 and 4 weeks of age with no detrimental effects. Dependent on the level of production, animals can be weaned at 2 or 4 weeks depending on the operators desired litters per year.